Relative calorific value of some coals on Kansas markets - Fay, Scott Stuart (My University, 1905)
Introduction: The fuel value of coals, while it is a subject that hitherto has attracted but little attention, is one that the engineers of today are beginning to consider seriously; but it is not only these thoughtful engineers that are wide awake to the question, but practically all scientists as well, and even many coal dealers, and to a less extent the general public. Ordinarily coal is priced not on its real or its practical value as a producer of heat, but on an entirely different basis, namely, the cost necessary to lay it down, on the market. After calculating the expenditure, of wealth in mining, transportation, storing and a reasonable: profit for all concerned, and considering nothing more its market value is determined. Now this, while it must need be borne in mind, is not the principal item be used in ascertaining their commercial values. Since coal is used for the production of energy the all-important question in rating the article should be how much energy will it produce compared with others? It is to be hoped that further investigation will revise this, and give us a more scientific price list. Certainly it would be a valuable piece of work that would assign each its proper place in the system. It is the object of this experiment to arrive at some conclusions regarding the calorific value of a few coals on Kansas markets. Of the fourteen samples used thirteen were obtained from the dealers, while the other one the college coal coming from Lansing is not on the market at all. Sampling was done in the manner about to be described: A sample filling an ordinary coal bucket was taken from various parts of the bin. This was broken into small pieces, not larger than walnuts, and then spread out upon the sampling table, letting each shovel- full fall upon the same spot giving each particle an equal opportunity to roll in the direction and to the distance it would.
Citation: Fay, Scott Stuart. Relative calorific value of some coals on Kansas markets. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Sammpling; Instrument Method of Calculation; Correction for Water Content; Theses